1998
DOI: 10.1086/305783
|View full text |Cite
|
Sign up to set email alerts
|

Observations of BL Lacertae from the Geodetic VLBI Archive of the Washington Correlator

Abstract: We present maps of BL Lac obtained from geodetic VLBI data from the archive of the Washington correlator. The observations were made from 1996 March to 1996 November, with periods from one experiment to another as short as 1 month. The dominant structure of the maps is given by a superluminal component (C2) moving predominantly at position angle D190¡. At the later epochs a new superluminal component (C3) emerges from the core and moves along a trajectory at a higher position angle (200¡). We also include maps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 15 publications
2
36
0
Order By: Relevance
“…The most promising models are the binary black hole model and the perturbation model. The helical jet related to the binary black holes have been used to explain the optical behaviour and objects (3C 345, OJ 287, BL Lacertae, and PKS 0735+178), thought to show periodicity in the historic light curves, also show helical trajectories of their VLBI radio components (Hardee 1987;Vicente et al 1996;Tateyama et al 1998;Gomez et al 1999;Villata & Raiteri 1999). In this sense, we would expect the similar VLBI observation results for other sources presented here.…”
Section: Discussionsupporting
confidence: 80%
“…The most promising models are the binary black hole model and the perturbation model. The helical jet related to the binary black holes have been used to explain the optical behaviour and objects (3C 345, OJ 287, BL Lacertae, and PKS 0735+178), thought to show periodicity in the historic light curves, also show helical trajectories of their VLBI radio components (Hardee 1987;Vicente et al 1996;Tateyama et al 1998;Gomez et al 1999;Villata & Raiteri 1999). In this sense, we would expect the similar VLBI observation results for other sources presented here.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, VLBA/VLBI studies of the jet structure in AGNs have revealed bent jet morphologies that are suggestive of streaming motions along a helical path (see e.g. Lister 2001) or that the magnetic field may present a helical geometry (Gabuzda et al 2004); this is also true for BL Lacertae (Tateyama et al 1998;Denn et al 2000;Marscher et al 2008;O'Sullivan & Gabuzda 2009, see also Stirling et al 2003). Moreover, a rotating helical path in a curved jet was invoked by Villata et al (2009) to explain the optical and radio behaviour of BL Lacertae in the last forty years, in particular the alternation of enhanced and suppressed optical activity, accompanied by hard and soft radio events, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, X-ray, VLBA, and VLBI observations of the distorted jets in PKS 1510-089 provide important evidence for the presence of the SMBBH in its nucleus. On the other hand, one notes that the light curves of all pioneering discoveries of the SMBBH show only periodic outbursts, such as OJ 287 (Sillanpää et al 1988(Sillanpää et al , 1996Valtonen 2007), 3C 345 (Webb et al 1988;Zhang et al 1998), BL Lac (Tateyama et al 1998;Fan et al 1998), 3C 454.3 (Li et al 2006, PKS 0735+178 (Smith et al 1987;Ding et al 2004;Ciprini et al 2007), Mkn 421 (Xie et al 1998a;Liu et al 1997). In addition, periodic light curves in AGNs are often attributed to the presence of SMBBHs (Komossa 2003;Merritt & Milosavljević 2005).…”
Section: Discussionmentioning
confidence: 99%